The 'refugee' and the 'nexus' requirement: The relation between subject and persecution in the United Nations Refugee Convention - Nilsson, Eva (Women's studies international forum, 2014)
The challenge that my paper deals with is the complexities of gender and violence within international refugee law, taking women exposed to male partner violence as a starting point. The focus is the definition of 'refugee' in the United Nations Refugee Convention and the requirement that the persecution must be based on specific grounds, the 'nexus' requirement. My analysis shows that the Convention is grounded in an essentialist understanding of the subject and that the preservation of its structure and integrity also means preserving the power structures in society. The argumentation suggests that it is time to abolish the 'nexus' requirement and the limitation of the grounds, but my conclusion is rather that we must continue to work with our frame of thought focusing on the 'refugee situation' and the discursive constitution of the subject in time and space.